Euphorbia flavicoma subsp. bermejense (Euphorbiaceae): a new obligate serpentinophyte from the southern Iberian Peninsula. - Hidalgo-Triana, Noelia; Pérez-Latorre, Andrés Vicente; Cabezudo-Artero, Baltasar (Magnolia Press, 2016)
A new subspecies of the genus Euphorbia is described and illustrated. The new taxon occurs on rocky peridotite soils as an endemism forming part of the serpentine open scrublands in the province of Malaga (southern Iberian Peninsula, Spain). The only population belonging to this new taxon was formerly identified as E. flavicoma subsp. giselae, which also lives in the south of France. The new subspecies can now be separated from the French population and from E. flavicoma subsp. flavicoma by several characters: biological type, pubescence, margin and lamina shape and ecology.
Política de acceso abierto (básicamente, no tiene) tomada de: https://v2.sherpa.ac.uk/id/publication/4
Keywords: Euforbiáceas - Clasificación; Euphorbia; Peridotite